Assessing hyperglycemia avoidance in people with Type 1 diabetes. (May 2014) - Singh, Harsimran; Gonder-Frederick, Linda; Schmidt, Karen; Ford, Derek; Vajda, Karen A; Hawley, Jeffrey; Cox, Daniel J
SUMMARY: : Aims: People with anxieties related to high blood glucose may engage in avoidance behaviors that increase their risk of hypoglycemia. Conversely, reduced concern about hyperglycemia could impair diabetes control. We developed the Hyperglycemia Avoidance Scale (HAS) to assess the extent of potentially problematic avoidant attitudes and behaviors in people with Type 1 diabetes (T1D).Materials & Methods: The HAS was administered to 501 people with T1D (mean age: 43 years). Data analysis included Exploratory Factor Analysis (EFA) using polychoric correlations and Item Response Theory. Relationships between the HAS and other diabetes-related measures were examined.Results: The EFA supported a 22-item, four-factor solution with excellent item reliability for all factors. HAS factors were found to be predictive of prospective S Hand prospective driving mishaps. Higher HbA1c values were also significantly related to the HAS. Pump users reported significantly greater avoidance of hyperglycemia than their counterparts.Conclusions: The HAS reliably quantifies affective and behavioral aspects of hyperglycemia avoidance. Future studies are encouraged to determine the usefulness of the scale with other more diverse populations with diabetes.